HEAT TRANSFER ANALYSIS OF WINGLET TYPE FINS ARRAY THROUGH NATURAL CONVECTION - MR. M. M. DEOGHARE; PROF. K. R. SONTAKKE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Fins are the extended surfaces used for increase heat transfer rate by convection method. In method of natural convection generally fins used should be of rectangular or circular shape, for intension to dissipate more heat to surrounding and maintain valuable components, parts safe and cool. From study of research paper it should be clear that the fins used for the heat dissipation should not arrange in large number in regulated space. In natural convection the air move along the fins as per buoyancy concept so that the air move upward when it becomes comes in contact with fins and lighter, but logical thing is that the natural air movement carried out in all direction there is no particular direction of air to strike the fin wall that means , air inlet direction is not fixed but the outlet becomes fixed. In case of horizontal based fins array when air strike to fins and heat transfer with these air but hot air trapped in between two fins and transfer rate of heat decreases, also in case of vertical based fins there is problem introduced of boundary layer development, so that fins with large fin height should not be used. To overcome above difficulties in natural convection to transfer heat effectively from plate to introduced winglet type fins array, because of winglet shape of fins air strike to fin wall in any condition of movement of air because the fins are inclined to both horizontal and vertical direction so that the heat transfer from fns is logically more than two cases but it interesting to investigate winglet angle of fins for more heat transfer by natural convection method.